The Documentation Centre of the FAL and Integration Information System University - Editora, La (1982)
After a wide process of reflection one believes the Center of Documentation of the Faculty of Philosophy and Letters. His intention is trasmitir knowledge and to promote the development of knowledge by means of the employment of modern technologies of investigation.